A SUMMER TANAGER PIRANGA RUBRA ANNIHILATES A WASP NEST - TORO, MIGUEL A DEL (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
A female grabbed individual wasps from nest for about 3 hrs until all adult wasps left, then gorged itself on the larvae and pupae Process repeated next day also ABSTRACT AUTHORS: L M Bartlett
ZEITSCHRIFT FUR ERD VOLKER UND STAATENKUNDE
Keywords: SUMMER TANAGER, PIRANGA RUBRA, ANNIHILATES, WASP NEST; CIENCIAS AGRARIAS; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL